1988
DOI: 10.1111/j.1399-3054.1988.tb06620.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and carbohydrate partitioning in sweet cherry: Fruiting effects

Abstract: The effect of fruiting on carbon fixation and retention in leaves was monitored by measuring net photosynthesis (Pn) and total non‐structural carbohydrates (TNC) on a seasonal basis on mature fruiting and non‐fruiting sweet cherry trees (Prunus avium L. cv. Bing). Pn was also measured diurnally during stages II and III of fruit development. Pn rates increased to between 18 and 20 mg CO2 dm‐2 h‐1 during stage II of fruit development and were maintained until harvest. Diurnally, Pn increased in the morning to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
56
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 25 publications
6
56
2
Order By: Relevance
“…The similarity in the patterns of Pn within a main-stem node for leaves which developed during different growth stages suggests that boll initiation does not alter leaf Pn. These observations are in agreement with Constable and Rawson (1980) and others (Crafts-Brander and Poneleit, 1987; Roper et al, 1988) in cotton, corn and sweet cherry.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The similarity in the patterns of Pn within a main-stem node for leaves which developed during different growth stages suggests that boll initiation does not alter leaf Pn. These observations are in agreement with Constable and Rawson (1980) and others (Crafts-Brander and Poneleit, 1987; Roper et al, 1988) in cotton, corn and sweet cherry.…”
Section: Discussionsupporting
confidence: 82%
“…Although this is a somewhat atypical situation in cotton due to the high probability of boll abscission, it does provide an ideal opportunity to observe potential fruiting effects on Pn. Recent evidence suggests that fruit development in sweet cherry and cotton might affect the Pn of subtending leaves (Roper et al, 1988;Wells, 1988). Wells (1988) presented information that cotton leaves which emerged during vegetative growth had higher Pn levels than those present in leaves which emerged during periods of fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that, although all the measurements were performed at the pre-flowering stage, some of the non-inoculated well-irrigated plants ( ÀV) were close to swell floral buds. Such a phenological difference between plants may explain the great variability of some photosynthetic parameters, such as A and g s , in the treatment À V. Flowering-associated decreases in A and g s have been observed in Prunus avium L. (Roper et al, 1988) and, more recently, in Mangifera indica L. (Urban et al, 2004(Urban et al, , 2008. Comparing the response of gas exchange and Chl fluorescence parameters (A, Ci, ETR and F v /F m ) to Verticillium infection and soil drought, it must be noted that, in general, the effect of the fungus was mimicked by soil water deficit (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…Apple, and to a lesser extent grape, are fruits that appear to demonstrate this fruiting effect most clearly (Wibbe et al, 1993;Wunsche et al, 2000;Downton et al, 1987), whereas no conclusive results have been reported in the literature with respect to other fruit tree species such as peach or cherry. Even in the case of apple, not all reports suggest the same positive response (e.g., Proctor et al, 1976;Roper et al, 1988;Schechter et al, 1994). It is now believed that photosynthetic responses at the whole canopy level are modulated by carbohydrate demand, and that previously conflicting reports on apple arose because experiments were carried out under conditions in which the fruit had a low carbon demand (Wunsche and Ferguson, 2005).…”
mentioning
confidence: 92%